Population pharmacokinetic modeling of itraconazole and hydroxyitraconazole for oral SUBA-itraconazole and sporanox capsule formulations in healthy subjects in fed and fasted states - Abuhelwa, Ahmad Y; Foster, David J R; Mudge, Stuart; Hayes, David; Upton, Richard N (Antimicrobial agents and chemotherapy, 2015)
Itraconazole is an orally active antifungal agent that has complex and highly variable absorption kinetics that is highly affected by food. This study aimed to develop a population pharmacokinetic model for itraconazole and the active metabolite hydroxyitraconazole, in particular, quantifying the effects of food and formulation on oral absorption. Plasma pharmacokinetic data were collected from seven phase I crossover trials comparing the SUBA-itraconazole and Sporanox formulations of itraconazole. First, a model of single-dose itraconazole data was developed, which was then extended to the multidose data. Covariate effects on itraconazole were then examined before extending the model to describe hydroxyitraconazole. The final itraconazole model was a 2-compartment model with oral absorption described by 4-transit compartments. Multidose kinetics was described by total effective daily dose- and time-dependent changes in clearance and bioavailability. Hydroxyitraconazole was best described by a 1-compartment model with mixed first-order and Michaelis-Menten elimination for the single-dose data and a time-dependent clearance for the multidose data. The relative bioavailability of SUBA-itraconazole compared to that of Sporanox was 173% and was 21% less variable between subjects. Food resulted in a 27% reduction in bioavailability and 58% reduction in the transit absorption rate constant compared to that with the fasted state, irrespective of the formulation. This analysis presents the most extensive population pharmacokinetic model of itraconazole and hydroxyitraconazole in the literature performed in healthy subjects. The presented model can be used for simulating food effects on itraconazole exposure and for performing prestudy power analysis and sample size estimation, which are important aspects of clinical trial design of bioequivalence studies.